Determinants of Willingness to Use Mobile Payment Application in China - Chen, Shulan; Chaiyasoonthorn, Wornchanok; Chaveesuk, Singha (My University, 2024)
During the past 20 years, the Gross Domestic Product (GDP) has shown rapid growth in China. By 2022, the Chinese GDP has reached 121.02 trillion yuan, 12 times that of 2000. The rapid development of the Chinese economy has further improved the living standards of the Chinese. At the same time, the Chinese demand for transaction payments is increasing daily, and the people's requirements for transaction payments are also getting higher and higher. The growth of demand for transaction payment boosts the development of the mobile payment industry, which provides opportunities for the mobile payment market. At the same time, there are increasing types of mobile payment in the market, and the competition is becoming increasingly fierce, which brings challenges and difficulties to mobile payment operators. The purpose of this study is to build a model framework to help Chinese mobile payment operators identify factors that affect consumers’ use of mobile payment to expand consumer groups and enhance the competitiveness of mobile payment companies. The novelty of this study is that, based on the SOR theory, the paper constructs a conceptual framework of mobile payment application users’ willingness to use in China and finds out the key factors of willingness to use mobile payment. The study results show that the key factors influencing willingness to use mobile payment are usefulness, ease of use, service quality, cost, risk, perceived value, and satisfaction.
Keywords: China; Mobile payment application; S-O-R theory; Willingness to use